Isolation and structure of a cDNA expressing a mammalian 3-methyladenine-DNA glycosylase. - O'Connor, T R (1990)
A cDNA plasmid expression library was constructed from the poly(A)+ mRNA of H4 cells, a rat hepatoma cell line. The library was introduced into Escherichia coli strain BH290 deficient in the repair of 3-methyladenine (3-meAde) residues in DNA. This DNA repair deficiency renders the stain phenotypically sensitive to treatment with alkylating agents. The cDNA library was screened for survivors to methylmethane sulfonate. BH290 cells hosting one of the plasmids, pAPDG10 (Alkylated N-Purine-DNA Glycosylase), from surviving cells had a sensitivity to MMS equivalent to that of the wild type strain. Crude extracts of BH290 cells harboring the pAPDG10 plasmid released 3-meAde and 7-methylguanine residues from DNA methylated with [methyl-3H]dimethylsulfate. The cDNA sequence of 993 bp inserted in pAPDG10 has a single open reading frame greater than 85 amino acids in length. The derived APDG protein sequence of 253 amino acids and the 3-meAde-DNA glycosylase II of E. coli coded for by the alkA gene have regions of conserved sequences. Analysis of the genomic DNA using Southern hybridization suggests that the APDG gene has a minimal size of 6.5-12 kb. Northern blot analysis shows that the transcript produced in H4 cells is also present in normal rat liver cells.